Household Mealtimes During the 2020 COVID-19 Lockdown in Aotearoa New Zealand: The Influence of Household Type and Psychological Distress - Egli, Victoria; Hunter, Lauren; Roy, Rajshri; Te Morenga, Lisa; De Backer, Charlotte; Teunissen, Lauranna; Cuykx, Isabelle; Decorte, Paulien; Gerritsen, Sarah (Frontiers in Nutrition, 2022)
Covid-19 lockdown meant disruptions to daily routines for households in Aotearoa New Zealand. The research presented here investigates how mealtimes changed for people living in New Zealand during the first Covid-19 lockdown in mid-2020 and sought to determine if household composition type and psychological distress impacted the frequency of engaging in several mealtime behaviors. The Covid Kai Survey collected data using an anonymous, online survey and asked questions on sociodemographic characteristics including household composition, frequency of engaging in different mealtime behaviors before and during lockdown, and psychological distress, which was measured using the Kessler 6 screening tool. The findings of this study shows an increase in the perceived importance of mealtimes (n=807, 26.9% before lockdown, n= 1154, 38.5% during lockdown) and an increase in the proportion of the survey respondents who stated that they frequently ate meals at the dinner table (n=1343, 44.8% before lockdown, n= 1481, 49.4% during lockdown). There was a decrease, across all household composition types, in the proportion of respondents who ate out frequently at a restaurant or café (n=878, 29.3% before lockdown, n=5, 0.2% during lockdown). The use of meal kits, e-dining, and eating meals in front of screens is also presented and discussed. All results are discussed with reference to Aotearoa New Zealand’s stringent lockdown restrictions. Respondents who experienced psychological distress during lockdown were 1.47 more likely to consider mealtimes an important part of their day and respondents living in households with one adult and at least one child who also experienced psychological distress were 5.95 times more likely to eat dinner at the dinner table than those who did not report psychological distress. Findings of this study further the understanding of the wider societal impact of Covid-19 lockdown on everyday life.